Supplementary file to: Ship, M. and Robinson, L. (2012). "Permeating all community activities"?; comparing events and programming in Westminster and Tower Hamlets public libraries, Library and Information Research, 36 (113), 114126. (2012) - Ship, Meredith; Robinson, Lyn
No abstract available